Adherence in twice weekly therapy for childhood tuberculosis - Naude, James te Water (Department of Paediatrics and Child Health, 2018)
AIM: This thesis examines the adherence to therapy as part of a clinical trial to determine the effectiveness of fully intermittent therapy for childhood tuberculosis. OBJECTIVES: These were to determine 1) the effectiveness of fully twice weekly therapy in childhood pulmonary tuberculosis, 2) whether adherence rates would be affected by twice weekly dosing and 3) whether certain socio-demographic factors influenced adherence.